Neutrophilic Reversible Allograft Dysfunction (NRAD) and Restrictive Allograft Syndrome (RAS) - Verleden, Stijn E.; Vandermeulen, Elly; Ruttens, David; Vos, Robin; Vaneylen, Annemie; Dupont, Lieven J.; Van Raemdonck, Dirk E.; Vanaudenaerde, Bart M.; Verleden, Geert M. (Seminars in Respiratory and Critical Care Medicine, 2013)
Lung transplantation is currently considered as an ultimate live-saving treatment for selected patients suffering from end-stage pulmonary disease. Long-term survival, however, is hampered by chronic rejection, or chronic lung allograft dysfunction (CLAD). Recently, various phenotypes within CLAD have been identified, challenging the established clinical definition of bronchiolitis obliterans syndrome (BOS). Some patients with presumed BOS, for instance, demonstrate an important improvement in forced expiratory volume in the first second of expiration (FEV1) after treatment with azithromycin. These patients are characterized by the presence of excess (≥15%) bronchoalveolar lavage (BAL) neutrophils, in absence of concurrent infection. This phenotype of CLAD has been redefined as neutrophilic reversible allograft dysfunction (NRAD), and these patients generally have a very good prognosis after diagnosis. Another group of patients with CLAD develop a restrictive rather than an obstructive pulmonary function defect (defined as a decline in total lung capacity of at least 10%) and demonstrate persistent interstitial and ground-glass opacities on chest computed tomographic (CT) scan. This phenotype is called restrictive allograft syndrome (RAS), and patients with RAS have a much worse prognosis after diagnosis. This review further discusses both of these CLAD phenotypes that do not fit the classical definition of BOS. Potential pathophysiological mechanisms, etiology, diagnosis, prognosis, and treatments are discussed.
Keywords: neutrophilic reversible allograft dysfunction (NRAD); restrictive allograft syndrome (RAS); chronic lung allograft dysfunction; lung transplantation